Data and code for: Sequence specificity in DNA binding is mainly governed by association - Marklund, Emil; Mao, Guanzhong; Yuan, Jinwen; Zikrin, Spartak; Abdurakhmanov, Eldar; Deindl, Sebastian; Elf, Johan (Uppsala University, 2021)
Sequence-specific
binding of proteins to DNA is essential for accessing genetic
information. Here, we derive
a simple equation for target-site recognition, which uncovers a
previously unrecognized coupling between the macroscopic association and
dissociation rates of the searching protein. Importantly, this
relationship makes it possible to recover the relevant microscopic
rates from experimentally determined macroscopic ones. This post
contains kinetic data for the lac repressor and code to analyse and
interpret the data in light of this theory.

File list:- data_pbm.zip - Data-set for output generated using a protein binding microarray.
- data_tirf.zip - Data-set for output generated using TIRF based single molecule localisation microscopy.
- data_cas9.zip - Data-set for cas9 binding collected from literature.
- data_spr.zip - Data-set for output generated using surface plasmon resonance based methods.
- figure_scripts.zip - Set of scripts used to generate all figures. See README file inside for details.
Keywords: Animal physiology - biophysics; Human biophysics; Plant cell and molecular biology; Animal cell and molecular biology; Medical and Health Sciences; Medicin och hälsovetenskap; Molecular Biology; Molekylärbiologi; Biophysics; Biofysik